PENGEMBANGAN BAHAN AJAR CERAMAH BERTEMA BUDAYA KERJA 5R MENGGUNAKAN METODE PEMBELAJARAN RESITASI UNTUK SMK DI KABUPATEN PEKALONGAN - Muhammad Fakhri Rosyada; Harjito; Ika Septiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Vocational Schools as vocational schools aim to prepare graduates to be ready for work. This can be achieved through learning activities. Learning in vocational schools does not yet integrate work culture in every subject. One of the obstacles experienced was that the available teaching materials had not yet led to the cultivation of work culture, so lecture teaching materials were developed with the theme of 5R work culture. The formulation of the problem in this research is (1) what is the need for lecture teaching materials on the theme of 5R work culture using the recitation learning method for vocational schools in Pekalongan Regency? (2) What is the prototype of lecture teaching materials with the theme of 5R work culture using the recitation learning method for vocational schools in Pekalongan Regency? The aims of this research are (1) to determine the need for lecture teaching materials on the theme of 5R work culture using the recitation learning method for vocational schools in Pekalongan Regency, (2) to produce a prototype of lecture teaching materials on the theme of 5R work culture using the recitation learning method for vocational schools in Pekalongan Regency. This research is development research or Research and Development (R&D) using the modified Borg and Gall model. Usage trial research was carried out at SMK Muhammadiyah Bligo and SMK Negeri 1 Kedungwuni. The development stage consists of the teaching material development stage, validation of material experts and media experts, revision I, limited scale trial, revision II, trial use, and final revision. media experts got a percentage of 86%, which means that lecture teaching materials on the theme of 5S work culture are very suitable for use. The percentage of limited trial results by teachers at SMK Muhammadiyah Bligo was 86%. The percentage of test scores used by teachers was 97% and 100%. The average scores of students in carrying out evaluations in this teaching material were 87.60 and 89.81. Another result of this research is the finding that students gained a lot of new knowledge about the 5R work culture as seen from the response questionnaire and the highest task score, namely the task of finding the equivalent of 5R words in Japanese. The weakness in this teaching material lies in the design of the teaching material which is less attractive. Students who get lower grades are due to factors such as level of intelligence, interest and motivation.